Qu-Du-San-Jie decoction induces growth inhibition and vascular normalization in NF2-associated vestibular schwannoma - Lin, Jie; Li, Shi-Wei; Zhang, Jing; Chu, Fu-Hao; Li, Cheng-Ze; Bie, Zhi-Xu; Tang, Han-Lu; Gao, Shan; Li, Ping; Liao, Meng-Ting; Xin, Tian-Xi; Zhao, Fu; et al. (Frontiers in Pharmacology, 2022)
Background: Neurofibromatosis type 2 (NF2) is a rare genetic syndrome that predisposes individuals to develop bilateral vestibular schwannomas (VSs) causing a high risk of life-threatening neurological complications. Traditional treatment options for NF2-associated VS usually cause neurological damage, and to date, there are no FDA-approved pharmacotherapies for NF2. The aim of this study was to evaluate the antitumor efficacy of Qu-Du-San-Jie (QDSJ) decoction, a traditional Chinese medicine formula, on NF2-associated VS and to investigate the potential underlying mechanisms. Methods: Ultra high-performance liquid chromatography-mass spectroscopy (UHPLC-MS) analysis was performed to identify the components of QDSJ and their targets. To determine the relationships between the putative targets of QDSJ and the differential gene of NF2-associated VS, the drug-disease crossover genes were screened using the UHPLC-MS data combined with our previous gene expression profiling data. The differentially expressed genes were imported into the STRING database to generate a PPI network. Differentially expressed gene targets and pathways were identified using GO and KEGG pathway enrichment analyses. The in vitro and in vivo drug efficacy of QDSJ decoction was tested using a patient-derived Schwannoma cell line and a patient-derived xenograft mouse model, respectively. H&E staining, immunochemistry, and immunofluorescence staining were used to evaluate the cell proliferation and tumor vessels. Results: A total of 133 compounds were identified in QDSJ decoction using UHPLC-MS analysis. Network pharmacology showed that the regulation of necroptosis, apoptosis, cell cycle, angiogenesis, adherens junction, and neuroactive ligand-receptor interaction could be associated with the efficacy of QDSJ in treating NF2-associated vestibular schwannomas. Treatment with QDSJ induced necrotic cell death and apoptosis of schwannoma cells in vitro and suppressed the tumor growth in vivo. Histopathological analysis revealed areas of cell necrosis and enlarged tumor blood vessels in the QDSJ-treated tumors. The numbers of cells positive for Cyclin D1 and Ki-67 were significantly reduced in QDSJ-treated tumors compared to control tumors. Immunofluorescence staining of CD31 and αSMA showed a decreased number and density of tumor vessels and normalized vessel structure in QDSJ-treated tumors. Conclusion: Our study demonstrates that QDSJ decoction shows significant antitumor activity against NF2-associated schwannoma and is a possible candidate for future clinical trials.